Impact of climate change on the success of population support management and plant reintroduction at steep, exposed limestone outcrops in the German Swabian Jura - Koch, Marcus; Winizuk, Alexandra; Banzhaf, Peter; Reichardt, Jürgen (Perspectives in plant ecology, evolution and systematics, 2021)
Species-rich rocky outcrops and cliff vegetation in central Europe distributed outside alpine regions are typically associated with historical landscapes of interrelated natural and cultural features such as the Swabian Alb in Germany. Consequently, in these regions, biodiversity is highly threatened by various factors, such as land use change and increased land use intensity. In central Europe, the flagship species closely associated with these vegetation types is Cheddar Pink (Dianthus gratianopolitanus), whose total European population is declining. Herein, we exemplified a successful reintroduction experiment at two different sites at the species’ distribution center in Germany on the Swabian Alb. In total 549 individuals were reintroduced in 2017 and 2018 and monitored in the field until 2020. Using a subset of clonally replicated plants it was shown under controlled conditions in greenhouses during 2016-2019 that climate change and, in particular, increased temperature sum in late winter and during spring had a great effect on the phenology and population fitness of D. gratianopolitanus ex situ. It was demonstrated that these effects were independent of genetic variation and cultivation effects. Global climate change and increased temperature sums not only caused significant earlier flowering, but also significantly reduced number of flowers and seed set, thereby drastically affecting population viability in a negative way. We concluded that ecological micro-niches of the studied species are spatially shifting and that the germination and seedling phases will become increasingly crucial for its long-term population persistence. Our study has potential implications for future cliff management and successful long-term habitat protection strategies.
Gesehen am 06.12.2021